RETRACTED: Associations of vitamin D receptor polymorphisms with risk of Alzheimer’s disease, Parkinson’s disease, and mild cognitive impairment: a systematic review and meta-analysis - Yanjun Du; Peizhen Geng; Qunqun Chen; Laixi Han; Lu Liu; Maoquan Yang; Mingzhu Tan; Jun Meng; Xiaojuan Sun; Lidan Feng (Frontiers in Aging Neuroscience)
Vitamin D is a lipid soluble steroid hormone, which plays a critical role in the calcium homeostasis, neuronal development, cellular differentiation, and growth by binding to vitamin D receptor (VDR). Associations between VDR gene polymorphism and Alzheimer’s disease (AD), Parkinson’s disease (PD), and mild cognitive impairment (MCI) risk has been investigated extensively, but the results remain ambiguous. The aim of this study was to comprehensively assess the correlations between four VDR polymorphisms (FokI, BsmI, TaqI, and ApaI) and susceptibility to AD, PD, and MCI. Crude odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to determine the relationship of interest. Pooled analyses suggested that the ApaI polymorphism decreased the overall AD risk, and the TaqI increased the overall PD susceptibility. In addition, the BsmI and ApaI polymorphisms were significantly correlated with the overall MCI risk. Stratified analysis by ethnicity further showed that the TaqI and ApaI genotypes reduced the AD predisposition among Caucasians, while the TaqI polymorphism enhanced the PD risk among Asians. Intriguingly, carriers with the BB genotype significantly decreased the MCI risk in Asian descents, and the ApaI variant elevated the predisposition to MCI in Caucasians and Asians. Further studies are need to identify the role of VDR polymorphisms in AD, PD, and MCI susceptibility.